Corpo, corporeidade e práticas pedagógicas da educação física em escolas de ensino fundamental II na Região do Planalto em Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
Corporeality is an existential condition of human beings and leads us to discuss the relevance of its approach in pedagogical practice. This research sought to understand the relationship between the conceptions of body and corporeality of PE teachers in elementary school II, from the plateau region in the city of Santarém-PA, with their pedagogical teaching practices. The adopted methodology involved a bibliographic review of scientific production on the subject of body and corporeality and field research. For the production of data, generating questions that provoked in the participants conceptions about the investigated phenomenon were used. This research had the participation of 11 teachers graduated in Physical Education who work in centers of Elementary School II, in the plateau, in the municipality of Santarém, state of Pará. For the analysis, the Technique of Elaboration and Analysis of Units of Meanings. The results showed that teachers attribute two conceptions to the body: one that configures itself as dualist when making a dichotomy between body and mind, and another that alludes to corporeality, although the latter is not clearly and specifically presented in the reports of experiences of the Participants, however, pointed out elements, traits that characterize the relationship between the body and its surroundings in a perspective of preparing the student to act in society, relating the experiences in Physical Education classes with their reality, seeking to perceive the world, critically and citizenship.
Keywords: Corpo; Corporeidade; Educação; Educação Física Escolar; Prática pedagógica; CNPQ::CIÊNCIAS HUMANAS; FORMAÇÃO HUMANA EM CONTEXTOS FORMAIS E NÃO FORMAIS NA AMAZÔNIA